Regional Multiple Pathology Scores Are Associated with Cognitive Decline in Lewy Body Dementias. (30th October 2014) - Howlett, David R.; Whitfield, David; Johnson, Mary; Attems, Johannes; O'Brien, John T.; Aarsland, Dag; Lai, Mitchell K.P.; Lee, Jasinda H.; Chen, Christopher; Ballard, Clive; Hortobágyi, Tibor; Francis, Paul T.
Abstract Dementia with Lewy bodies (DLB) and Parkinson's disease dementia (PDD) are characterized by the presence of α‐synuclein‐containing Lewy bodies and Lewy neurites. However, both dementias also show variable degrees of Alzheimer's disease (AD) pathology (senile plaques and neurofibrillary tangles), particularly in areas of the cortex associated with higher cognitive functions. This study investigates the contribution of the individual and combined pathologies in determining the rate of cognitive decline. Cortical α‐synuclein, phosphorylated tau (phosphotau) and Aβ plaque pathology in 34 PDD and 55 DLB patients was assessed semi‐quantitatively in four regions of the neocortex. The decline in cognition, assessed by Mini Mental State Examination, correlated positively with the cortical α‐synuclein load. Patients also had varying degrees of senile Aβ plaque and phosphotau pathology. Regression analyses pointed to a combined pathology (Aβ plaque plus phosphotau plus α‐synuclein‐positive features), particularly in the prefrontal cortex (BA9) and temporal lobe neocortex with the superior and middle temporal gyrus (BA21, 22), being a major determining factor in the development of dementia. Thus, cognitive decline in Lewy body dementias is not a consequence of α‐synuclein‐induced neurodegeneration alone but senile plaque and phosphorylated tau pathology also contribute to the overall deficits.